ПРОБЛЕМА ФОРМУВАННЯ НАЦІОНАЛЬНОЇ ПОЛІТИЧ0 НОЇ ЕЛІТИ В ІСТОРИЧНІЙ ЛІТЕРАТУРІ: НЕРАДЯНСЬКА ІСТОРІОГРАФІЯ УКРАЇНСЬКОГО ПОЛІТИЧНОГО РУХУ В РОСІЙСЬКІЙ ІМПЕРІЇ (191701991 РР.) (Zaporizhzhia Historical Review, 2021)
In the paper such problem as non-soviet historiography of the Ukrainian political movement in Russian empire in the context of the national political elite forming has been analyzed. Changes in the author contingent, themes, source base and research methodology which took place during 1917-1991 are traced back.